2018
DOI: 10.15698/mic2018.06.634
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR conundrum: evolve and maybe die, or survive and risk stagnation

Abstract: CRISPR-Cas represents a prokaryotic defense mechanism against invading genetic elements. Although there is a diversity of CRISPR-Cas systems, they all share similar, essential traits. In general, a CRISPR-Cas system consists of one or more groups of DNA repeats named CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats), regularly separated by unique sequences referred to as spacers, and a set of functionally associated cas (CRISPR associated) genes typically located next to one of the repeat arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…A search of the 564 non-redundant spacers from P. aeruginosa revealed 33 spacers with high-scoring matches to resistance genes in ResFinder's reference ARG (electronic supplementary material, tables S4 and S5). This is consistent with experimental laboratory studies that showed that spacers can be acquired from ARGs and impede their subsequent uptake [12,59]. To be functional for interference, the type I systems of P. aeruginosa require protospacer adjacent motifs (PAMs).…”
Section: (B) Species With Crispr-cas Vary In Acquired Antibiotic Resistance Genessupporting
confidence: 79%
See 1 more Smart Citation
“…A search of the 564 non-redundant spacers from P. aeruginosa revealed 33 spacers with high-scoring matches to resistance genes in ResFinder's reference ARG (electronic supplementary material, tables S4 and S5). This is consistent with experimental laboratory studies that showed that spacers can be acquired from ARGs and impede their subsequent uptake [12,59]. To be functional for interference, the type I systems of P. aeruginosa require protospacer adjacent motifs (PAMs).…”
Section: (B) Species With Crispr-cas Vary In Acquired Antibiotic Resistance Genessupporting
confidence: 79%
“…These segments of intruder DNA in the CRISPR loci are termed spacers and their complementary target sequences are known as protospacers. The CRISPR arrays are transcribed, processed into short CRISPR RNAs (crRNAs) and, through the formation of Cas ribonucleoprotein complexes and target recognition, lead to degradation of the invading element [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The biological underpinnings of the non-uniform phyletic spread of CRISPR-Cas systems remain to be elucidated. Considering the high horizontal mobility of CRISPR-cas loci, it appears likely that their loss or retention in prokaryotic genomes depends on the trade-off between the fitness cost that is determined, mostly, by auto-immunity and curtailment of horizontal gene transfer, and the benefits of defence conferred by adaptive immunity [79][80][81][82][83][84] . These benefits, most likely, depend on the abundance and diversity of viruses in specific habitats as well as the biology of host-parasite interactions in specific groups of microorganisms 85,86 .…”
Section: [H1] Distribution Of Crispr-cas Systemsmentioning
confidence: 99%
“…Bacteria in their natural environments are exposed to many invading genetic elements such as phages and plasmids. These elements can constitute mechanisms of horizontal gene transfer conferring valuable attributes to the recipient cells, while they can also provoke cell death 1 . Amongst various bacterial defense mechanisms against invading elements, CRISPR-Cas systems are unique since they confer adaptative immunity to the cells.…”
Section: Introductionmentioning
confidence: 99%